Loss-of-Function of a Tomato Receptor-Like Kinase Impairs Male Fertility and Induces Parthenocarpic Fruit Set - Takei, Hitomi; Shinozaki, Yoshihito; Yano, Ryoichi; Kashojiya, Sachiko; Hernould, Michel; Chevalier, Christian; Ezura, Hiroshi; Ariizumi, Tohru (Frontiers in Plant Science, 2019)
Parthenocarpy arises when an ovary develops into fruit without pollination/fertilization. The mechanisms involved in genetic parthenocarpy have attracted attention because of their potential application in plant breeding and also for their elucidation of the mechanisms involved in early fruit development. We have isolated and characterized a novel small parthenocarpic fruit and flower (spff) mutant in the tomato (Solanum lycopersicum) cultivar Micro-Tom. This plant showed both vegetative and reproductive phenotypes including dwarfism of floral organs, male sterility, delayed flowering, altered axillary shoot development, and parthenocarpic production of small fruits. Genome-wide single nucleotide polymorphism array analysis coupled with mapping-by-sequencing using next generation sequencing-based high-throughput approaches resulted in the identification of a candidate locus responsible for the spff mutant phenotype. Subsequent linkage analysis and RNA interference-based silencing indicated that these phenotypes were caused by a loss-of-function mutation of a single gene (Solyc04g077010), which encodes a receptor-like protein kinase that was expressed in vascular bundles in young buds. Cytological and transcriptomic analyses suggested that parthenocarpy in the spff mutant was associated with enlarged ovarian cells and with elevated expression of the gibberellin metabolism gene, GA20ox1. Taken together, our results suggest a role for Solyc04g077010 in male organ development and indicate that loss of this receptor-like protein kinase activity could result in parthenocarpy.